USABILITY AND ACCEPTANCE OF MALAYLEARNING: A GAME-BASED MOBILE APPLICATION FOR SECOND LANGUAGE VOCABULARY ACQUISITION - Hamzah, Hammuzamer Irwan; Chin, Yi Jing; Tuan Muda, Tuan Zalizam; Zaiyadi, Mohd Fairuz (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This developmental study addresses common difficulties faced by Universiti Utara Malaysia (UUM) foreign students in learning Malay, specifically grammar, vocabulary, and motivation, by focusing on the development and evaluation of MalayLearning, a game-based mobile application. The methodology adhered to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), incorporating Mayer's Multimedia Principles to refine instructional alignment. Evaluation involved a Formative Review by content and multimedia experts to verify usability, followed by a Summative User Testing phase with five UUM foreign students to assess acceptance and user experience. While results from both evaluations consistently confirmed the application's high usability and clarity, the findings are presented as a qualitative proof-of-concept given the small sample size. The study concludes that MalayLearning serves as a validated pedagogical intervention for beginning Malay language acquisition, possessing significant potential to enhance autonomous learning outcomes through a blend of instructional design and motivational architecture.